Intercellular Adhesion Molecule-1 as Target for CAR-T-Cell Therapy of Triple-Negative Breast Cancer - Wei, Heng; Wang, Zeng; Kuang, Yi; Wu, Zhiguo; Zhao, Shasha; Zhang, Zongliang; Li, Hexian; Zheng, Meijun; Zhang, Nan; Long, Cheng; Guo, Wenhao; Nie, Chunlai; et al. (Frontiers in Immunology, 2020)
Triple-negative breast cancer (TNBC) comprises lethal malignancies with limited treatment options. Chimeric antigen receptor T (CAR-T) cell therapy is an effective immunotherapeutic strategy that has demonstrated unprecedented efficacy in the treatment of hematological malignancies but has shown limited success in the management of some solid tumors. Many malignant tumors are related to increased expression of intercellular adhesion molecule-1 (ICAM1), providing a rationale for ICAM1-specific immunotherapies for the treatment of cancer. Here, we validated the expression of ICAM1 in TNBC tissues. Subsequently, we generated a phage-displayed single-chain variable fragment (scFv) library using splenocytes from ICAM1-immunized mice and selected a novel ICAM1-specific scFv, mG2-scFv. Using mG2-scFv as the extracellular antigen binding domain, we constructed ICAM1-specific CAR-T cells and demonstrated the robust and specific killing of TNBC cell lines in vitro. Most importantly, in the TNBC mouse model, ICAM1-specific CAR-T cells significantly reduced the growth of the TNBC tumor, resulting in long-term remission and improved survival. Together, these results indicated that ICAM1-specific CAR-T cells have high therapeutic potential against ICAM1-positive TNBC tumors.